A history of chemical and biological weapons - Spiers, Edward M. (Reaktion Books, 2010)
Following the 9/11 attacks and the anthrax letters that appeared in their wake, the threat posed by the widespread accessibility of chemical and biological weapons has continually been used to stir public fear and opinion by politicians and the media alike. In Chemical and Biological Weapons, Edward M. Spiers cuts through the scare tactics and hype to provide a thorough and even-handed examination of the weapons themselves-the various types and effects-and their evolution from World War I to the present. Spiers describes the similarities and differences between the two types of weapons and how technological advancements have led to tactical innovations in their use over time. As well, he gives equal attention to the international response to the proliferation of chemical and biological weapons, analyzing global efforts aimed at restraining their use, such as deterrence and disarmament, and the effectiveness of these approaches in the twentieth century. Using Iraq as a case study, Spiers also investigates its deployment of chemical weapons in the Iran-Iraq War and the attempts by the international community to disarm Iraq through the United Nations Special Commission and the United States-led war in 2003. A timely and balanced historical survey, Chemical and Biological Weapons will be of interest to readers studying the proliferation and use of chemical and biological warfare and the reactions of the international community throughout the last several decades.